Cross-regional homeostatic and reactive glial signatures in multiple sclerosis - Trobisch, Tim; Zulji, Amel; Stevens, Nikolas; Schwarz, Sophia; Wischnewski, Sven; Öztürk, Mikail; Perales-Patón, Javier; Haeussler, Maximilian; Sáez Rodríguez, Julio; Velmeshev, Dmitry; Schirmer, Lucas (Acta neuropathologica, 2022)
Multiple sclerosis (MS) is a multifocal and progressive inflammatory disease of the central nervous system (CNS). However, the compartmentalized pathology of the disease affecting various anatomical regions including gray and white matter and lack of appropriate disease models impede understanding of the disease. Utilizing single-nucleus RNA-sequencing and multiplex spatial RNA mapping, we generated an integrated transcriptomic map comprising leukocortical, cerebellar and spinal cord areas in normal and MS tissues that captures regional subtype diversity of various cell types with an emphasis on astrocytes and oligodendrocytes. While we found strong cross-regional diversity among glial subtypes in control tissue, regional signatures become more obscure in MS. This suggests that patterns of transcriptomic changes in MS are shared across regions and converge on specific pathways, especially those regulating cellular stress and immune activation. In addition, we found evidence that a subtype of white matter oligodendrocytes appearing across all three CNS regions adopt pro-remyelinating gene signatures in MS. In summary, our data suggest that cross-regional transcriptomic glial signatures overlap in MS, with different reactive glial cell types capable of either exacerbating or ameliorating pathology.
Gesehen am 17.01.2023